Transmission electron microscopy and transdisciplinary research - Bürger, Julius; Lindner, Jörg K. N. (Climate Protection, Resource Efficiency, and Sustainable Mobility - Transdisciplinary Approaches to Design and Manufacturing Technology)

Transmission electron microscopy and transdisciplinary research - Bürger, Julius; Lindner, Jörg K. N. (Climate Protection, Resource Efficiency, and Sustainable Mobility - Transdisciplinary Approaches to Design and Manufacturing Technology)

Transmission electron microscopy and transdisciplinary research - Bürger, Julius; Lindner, Jörg K. N. (Climate Protection, Resource Efficiency, and Sustainable Mobility - Transdisciplinary Approaches to Design and Manufacturing Technology)

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos, Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg K.N. (Advanced Materials Interfaces)
Keywords: General Medicine

Selective Area Growth of Cubic Gallium Nitride in Nanoscopic Silicon Dioxide Masks - Meier, Falco; Littmann, Mario; Bürger, Julius; Riedl, Thomas; Kool, Daniel; Lindner, Jörg; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos de Pedro, Maria Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: General Medicine

Quality or Quantity? How Structural Parameters Affect Catalytic Activity of Iron Oxides for CO Oxidation - Schlicher, Steffen; Prinz, Nils; Bürger, Julius; Omlor, Andreas; Singer, Christian; Zobel, Mirijam; Schoch, Roland; Lindner, Jörg K. N.; Schünemann, Volker; Kureti, Sven; Bauer, Matthias (Catalysts)
<The replacement of noble metal catalysts by abundant iron as an active compound in CO oxidation is of ecologic and economic interest. However, improvement of their catalytic performance to the same level as state-of-the-art noble metal catalysts requires an in depth understanding of their working principle on an atomic level. As a contribution to this aim, a series of iron oxide catalysts with varying Fe loadings from 1 to 20 wt% immobilized on a γ-Al2O3 support is presented here, and a multidimensional structure–activity correlation is established. The CO oxidation activity is correlated to structural details obtained by various spectroscopic, diffraction, and microscopic methods, such as PXRD, PDF analysis, DRUVS, Mössbauer spectroscopy, STEM-EDX, and XAS. Low Fe loadings lead to less agglomerated but high percentual amounts of isolated, tetrahedrally coordinated iron oxide species, while the absolute amount of isolated species reaches its maximum at high Fe loadings. Consequently, the highest CO oxidation activity in terms of turnover frequencies can be correlated to small, finely dispersed iron oxide species with a large amount of tetrahedrally oxygen coordinated iron sites, while the overall amount of isolated iron oxide species correlates with a lower light-off temperature.
Keywords: Physical and Theoretical Chemistry; Catalysis; General Environmental Science; Key

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg K. N.; Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)
Keywords: Spectroscopy; General Materials Science

Characterisation of the PS-PMMA Interfaces in Microphase Separated Block Copolymer Thin Films by Analytical (S)TEM - Bürger, Julius; Kunnathully, Vinay; Kool, Daniel; Lindner, Jörg; Brassat, Katharina (Nanomaterials)
Block copolymer (BCP) self-assembly is a promising tool for next generation lithography as microphase separated polymer domains in thin films can act as templates for surface nanopatterning with sub-20 nm features. The replicated patterns can, however, only be as precise as their templates. Thus, the investigation of the morphology of polymer domains is of great importance. Commonly used analytical techniques (neutron scattering, scanning force microscopy) either lack spatial information or nanoscale resolution. Using advanced analytical (scanning) transmission electron microscopy ((S)TEM), we provide real space information on polymer domain morphology and interfaces between polystyrene (PS) and polymethylmethacrylate (PMMA) in cylinder- and lamellae-forming BCPs at highest resolution. This allows us to correlate the internal structure of polymer domains with line edge roughnesses, interface widths and domain sizes. STEM is employed for high-resolution imaging, electron energy loss spectroscopy and energy filtered TEM (EFTEM) spectroscopic imaging for material identification and EFTEM thickness mapping for visualisation of material densities at defects. The volume fraction of non-phase separated polymer species can be analysed by EFTEM. These methods give new insights into the morphology of polymer domains the exact knowledge of which will allow to improve pattern quality for nanolithography.
Keywords: General Materials Science; General Chemical Engineering

Influence of lens aberrations, specimen thickness and tilt on differential phase contrast STEM images - Bürger, Julius; Riedl, Thomas; Lindner, Jörg (Ultramicroscopy)
Keywords: Instrumentation; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Spray coating of poly(acrylic acid)/ZnO tetrapod adhesion promoting nanocomposite films for polymer laminates - Meinderink, Dennis; Nolkemper, Karlo J.R.; Bürger, Julius; Orive, Alejandro G.; Lindner, Jörg K.N.; Grundmeier, Guido (Surface and Coatings Technology)

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg K N; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Keywords: Electrical and Electronic Engineering; Mechanical Engineering; Mechanics of Materials; General Materials Science; General Chemistry; Bioengineering

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)
DNA origami nanostructures are versatile substrates for the controlled arrangement of molecular capture sites with nanometer precision and thus have many promising applications in singlemolecule bioanalysis. Here, we investigate the adsorption of DNA origami nanostructures in nanohole arrays which represent an important class of biosensors and may benefit from the incorporation of DNA origami-based molecular probes. Nanoholes with well-defined diameter that enable the adsorption of single DNA origami triangles are fabricated in Au films on Siwafers by nanosphere lithography. The efficiency of directed DNA origami adsorption on the exposed SiO2 areas at the bottoms of the nanoholes is evaluated in dependence of various parameters, i.e., Mg2+ and DNA origami concentrations, buffer strength, adsorption time, and nanohole diameter. We observe that the buffer strength has a surprisingly strong effect on DNA origami adsorption in the nanoholes and that multiple DNA origami triangles with 120 nm edge length can adsorb in nanoholes as small as 120 nm in diameter. We attribute the latter observation to the low lateral mobility of once adsorbed DNA origami on the SiO2 surface, in combination with parasitic adsorption to the Au film. While parasitic adsorption can be suppressed by modifying the Au film with a hydrophobic self-assembled monolayer, the limited surface mobility of the adsorbed DNA origami still leads to poor localization accuracy in the nanoholes and results in many DNA origami crossing the boundary to the Au film even under optimized conditions. We discuss possible ways to minimize this effect by varying the composition of the adsorption buffer, employing different fabrication conditions, or using other substrate materials for nanohole array fabrication.

On the Adsorption of DNA Origami Nanostructures in Nanohole Arrays - Brassat, Katharina; Ramakrishnan, Saminathan; Bürger, Julius; Hanke, Marcel; Doostdar, Mahnaz; Lindner, Jörg; Grundmeier, Guido; Keller, Adrian (Langmuir)

Nanostructure Research using Transmission Electron Microscopy at the new OWL Analytic Centre - Riedl, Thomas; Bürger, Julius; Kunnathully, Vinay; Wiegand, Marie; Duschik, K.; Ramermann, D.; Ennen, I.; Hertle, Y.; Schaper, Mirko; Hellweg, T.; Hütten, A.; Lindner, Jörg

Hierarchical nanopores formed by block copolymer lithography on the surfaces of different materials pre-patterned by nanosphere lithography - Brassat, Katharina; Kool, Daniel; Bürger, Julius; Lindner, Jörg (Nanoscale)
Bottom-up patterning techniques allow for the creation of surfaces with ordered arrays of nanoscale features on large areas. Two bottom-up techniques suitable for the formation of regular nanopatterns on different length scales are nanosphere lithography (NSL) and block copolymer (BCP) lithography. In this paper it is shown that NSL and BCP lithography can be combined to easily design hierarchically nanopatterned surfaces of different materials. Nanosphere lithography is used for the pre-patterning of surfaces with antidots, i.e. hexagonally arranged cylindrical holes in thin films of Au, Pt and TiO2 on SiO2, providing a periodic chemical and topographical contrast on the surface suitable for templating in subsequent BCP lithography. PS-b-PMMA BCP is used in the second self-assembly step to form hexagonally arranged nanopores with sub-20 nm diameter within the antidots upon microphase separation. To achieve this the microphase separation of BCP on planar surfaces is studied, too, and it is demonstrated for the first time that vertical BCP nanopores can be formed on TiO2, Au and Pt films without using any neutralization layers. To explain this the influence of surface energy, polarity and roughness on the microphase separation is investigated and discussed along with the wetting state of BCP on NSL-pre-patterned surfaces. The presented novel route for the creation of advanced hierarchical nanopatterns is easily applicable on large-area surfaces of different materials. This flexibility makes it suitable for a broad range of applications, from the morphological design of biocompatible surfaces for life science to complex pre-patterns for nanoparticle placement in semiconductor technology.

Micro- and nanopatterned surfaces with tailored chemical and topographical contrast by self-assembly techniques - Brassat, Katharina; Kool, Daniel; Bürger, Julius; Lindner, Jörg

Two-dimensional switchable blue phase gratings manufactured by nanosphere lithography - Wahle, M.; Brassat, Katharina; Ebel, J.; Bürger, Julius; Lindner, Jörg; Kitzerow, Heinz-Siegfried (Optics Express 25)
Switchable two dimensional liquid crystal diffraction gratings are promising can- didates in beam steering devices, multiplexers and holographic displays. For these areas of applications a high degree of integration in optical systems is much sought-after. In the context of diffraction gratings this means that the angle of diffraction should be rather high, which typically poses a problem as the fabrication of small grating periods is challenging. In this paper, we propose the use of nanosphere lithography (NSL) for the fabrication of two-dimensionally structured electrodes with a periodicity of a few micrometers. NSL is based on the self-assembly of micro- or nanometer sized spheres into monolayers. It allows for easy substrate structuring on wafer scale. The manufactured electrode is combined with a liquid crystalline polymer-stabilized blue phase, which facilitates sub-millisecond electrical switching of the diffraction efficiency at adiffractionangle of 21.4°.

Enzyme mediated autodeposition of protein particles on nanosphere lithographically nanostructured surfaces - Brassat, Katharina; Rüdiger, Arne; Bürger, Julius; Bremser, W.; Strube, Oliver; Lindner, Jörg

Arrangement of perovskitic semiconductor nanoparticles using soft lithography - Brassat, Katharina; Bürger, Julius; Reinecke, Melanie; Briese, Dennis; Duschik, K.; Schaper, Mirko; Lindner, Jörg

Site-selective protein immobilization on regular antidot patterns fabricated by nanosphere lithography - Brassat, Katharina; Rüdiger, Arne; Bürger, Julius; Bremser, W.; Strube, O.; Lindner, Jörg